Pengaruh NPL dan CAR Terhadap ROA pada Bank Umum Milik Negara - Mohamad Salman Sutrisno; Banter Laksana; Tjetjep Djuwarsa (Indonesian Journal of Economics and Management, 2022)
This study aims to determine the effect of Non Performing Loan (NPL) and Capital Adequacy Ratio (CAR) on Return on Asset (ROA). The population used in this study were state-owned commercial banks in 2013 – 2019. The research method used in this study was an associative research method with a quantitative approach. The data analysis technique used is multiple linear regression using IBM SPSS Statistic 26 for Windows. The results of this study partially show that Non Performing Loan (NPL) has a negative effect on Return on Asset (ROA) and significant, Capital Adequacy Ratio (CAR) has a positive effect on Return on Asset (ROA) and significant. Non Performing Loan and Capital Adequacy Ratio (CAR) also simultaneously or jointly have a significant effect on Return on Assets (ROA).